Mapping current research and future directions of Design Literacy with systematic quantitative literature review (SQLR) - Bolinas, Julius Cesar Fernandez (Design and Technology Education: An International Journal, 2022)
Design literacy is an emerging research field that is gaining attention among scholars today. Credit goes to the growing acceptance of design thinking in various disciplines beyond design. Design literacy develops natural abilities in everyone to solve real-world, wicked problems by supporting the cognitive development of concrete (making things) and iconic (making meanings) modes of cognition. The author argues for embedding design literacy in every educational level, particularly across disciplines in higher education. To gain insight into the state of scholarly discourse around design literacy in educational contexts, a systematic quantitative literature review (SQLR) was conducted using 12 databases to map its research direction and define its characteristics. The SQLR revealed several findings. First, the foundations of design literacy are grounded in general education and design education. Second, publications were meagre but well represented by the secondary and higher education level. Finally, two thematic directions were observed - design literacy for making things is the situated practice in secondary education while design literacy for making meanings is for higher education. This SQLR serves as a benchmark review and a starting point to initiate scholarly discourse on design literacy as it aims to contribute to the advancement of research in the field.